INTERPRETATION OF INDONESIAN COLONIAL HISTORY IN VISUAL ALLEGORY - Arumsari, Mangambar
History is an inseparable record of the past in the history of life. In theory, an academic study of history should always be based on facts, regardless of the biases or tendencies projected by the reviewers. Even so, there will always be gaps where history will meet interpretations that are ambiguous or subjective, depending on the background of each individual reviewer, the conclusions reached will certainly vary and remain bound by responsibility for truth. So what about the role of artists in responding to this problem? In this case, artists have the privilege of not being bound by the responsibility of conveying the most truthful facts of history. Works of art such as music, literature, fine art, and so on are mediums that can be used to convey the freedom of the artist. Artists can use their biases based on cultural identity, background, or ideology which can lead historical narratives in their creations to be in line with the intensity of what the artist want to convey or express. As an artist with an interest in colonial history, the author wants to use the opportunity in this final project to create the author's personal interpretation regarding the topic of Indonesian colonial history using visual language. Therefore, this series of final project is made as a means to provide such opportunity for the author.